Potential of Lactic Acid Bacteria Isolated from Fermented Tempe Food in Producing Fibrinolytic Enzymes - Amanda, Nifsa Riski; Hastuty, Aerma; Putri, Dwi Hilda; Sulistiani, Sulistiani (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Cardiovascular disease is the leading cause of death worldwide, mainly due to blood vessel blockage caused by thrombus. Fibrinolytic enzymes are used to dissolve thrombus but are often limited by high production costs, low specificity, allergic reactions, and bleeding risks. As a safer alternative, bacteria from fermented foods offer several advantages, including low toxicity, cost-effective production, and high fibrin specificity, which reduces the risk of bleeding. This study investigated the potential and characteristics of fibrinolytic enzyme activity produced by lactic acid bacteria (LAB) isolated from tempeh. The fibrin plate method was used to identify LAB producing the enzyme, while enzyme activity was measured using the method of Varol et al. (2023), and protein concentration was analyzed using a modified Bradford test. Thirteen LAB isolates showed fibrinolytic activity, with isolate PG01-2B selected as the most promising. The highest enzyme production occurred on the second day, reaching 83.41 U/mL. Characterization showed activity with acetic acid buffer pH 6 (102.18 U/mL) and at 75 minutes incubation time (99 U/mL). These results indicate that LAB from tempeh has strong potential as a source of fibrinolytic enzymes and can function as an alternative therapeutic agent for thrombus-related cardiovascular diseases.